THE ROLE OF VILLAGE HEALTH VOLUNTEERS (VHVS) IN PREVENTING THE CORONAVIRUS 2019 (COVID-19) OUTBREAK ACCORDING TO GOVERNMENT POLICY OF MUEANG DISTRICT SUPHANBURI PROVINCE - Chinnabutr, Wittaya; Phakdisorawit, Naphat (Journal of Buddhist Anthropology, 2021)
The Objectives of this research article were to 1) explore the roles of VHVs. for preventing the Coronavirus 2019, 2) comparing the roles of volunteers in the prevention of the Coronavirus 2019 disease outbreak by personal factors, and 3) to investigate the problems, obstacles, and guidelines for preventing the Coronavirus 2019 outbreak. This study is quantitative research, using a survey technique. The questionnaire was used as a research instrument to collect data from 230 village health volunteers of Mueang, Suphan Buri. The descriptive statistics implemented for data analysis include frequency, percentage, mean, standard deviation, T - test and F - test. The finding showed as follows: 1) village health volunteers (VHVs) performed considerable functions and roles overall. The perception of Coronavirus 2019 control and health promotion was reported highly, 2) village health volunteers (VHVs) whose main occupation are different played the different roles in the prevention of the Coronavirus 2019 outbreak, whereas sex, age, status, education level, average monthly income, length of service VHVs recruitment method are different played no different. and 3) problems and obstacles discovered include a lack of cooperation, namely, non-wearing of masks, non-social distancing, apparatus and equipment - a deficiency of instruments and equipment, people lack the understanding of COVID - 19 communicable disease, insufficient budget, and insufficient medical personnel whereas Problem solutions include that raising perception about the severity of the COVID - 19, increased support of government budget, educating people to understand the diseases development, causes and severity, and prevention and treatment, improving the communication potential, including providing public relations media in both version of Thai and foreign languages for correct understanding, and adequate supply of medical personnel and VHVs.